2011
DOI: 10.1245/s10434-011-1567-9
|View full text |Cite
|
Sign up to set email alerts
|

Msi-1 is a Predictor of Survival and a Novel Therapeutic Target in Colon Cancer

Abstract: Our study provides the basis to explore the use of Msi-1 as a novel prognostic biomarker in colon cancer patients. Aberrant overexpression of Msi-1 during metastasis of colon cancer also suggests that it is a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…Furthermore, a significant association was found between Msi-1 expression and overall survival in young patients. Our present findings in young patients with gastric cancer are consistent with studies of Msi-1 expression in other tumor types (23)(24)(25). In breast cancer patients, Msi-1 overexpression may be related to lymph node metastasis and shorter survival (23), and in human glioma, may be related to the degree of malignancy and proliferative activity (24).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, a significant association was found between Msi-1 expression and overall survival in young patients. Our present findings in young patients with gastric cancer are consistent with studies of Msi-1 expression in other tumor types (23)(24)(25). In breast cancer patients, Msi-1 overexpression may be related to lymph node metastasis and shorter survival (23), and in human glioma, may be related to the degree of malignancy and proliferative activity (24).…”
Section: Discussionsupporting
confidence: 90%
“…In breast cancer patients, Msi-1 overexpression may be related to lymph node metastasis and shorter survival (23), and in human glioma, may be related to the degree of malignancy and proliferative activity (24). In patients with colon cancer, Msi-1 is associated with advanced cancer stage, metastasis and poor survival (25). Knockdown of Msi-1 with Msi-1 siRNA resulted in reduced colon cancer cell proliferation, cancer growth arrest in xenografts, and increased apoptosis alone and in combination with radiation therapy in athymic nude mice in vivo (14).…”
Section: Discussionmentioning
confidence: 99%
“…As vascular and neural infiltrations are known to be ominous prognostic factors, their identification has great clinical relevance. Increasing evidence shows that perineural invasion or the neural cell adhesion molecule might be a prognostic factor for various cancers, such as bile duct cancer (Seki et al 1993, Kayahara et al 1994, gallbladder cancer (Seki et al 1995), breast cancer (Lo et al 1997), esophageal cancer (Tanaka et al 1998), pancreatic cancer (Pour et al 2003, Levy et al 2006, Kayahara et al 2007, prostate cancer (Li et al 2003), and colorectal cancer (Gavert et al 2005, Zhou et al 2009, Li et al 2011. Importantly, a recent report has shown that the severity of the neural invasion in rectal adenocarcinoma is an important factor in a scoring system to assess the prognostic value, showing high correlation with localization and severity (Ceyhan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Musashi-1 marker (Msi-1) is considered by some authors as a CSC marker in colon and stomach cancer (Kuang et al, 2013;Li et al, 2011). CD44 protein, which is an adhesion molecule, is also considered as a CSC marker.…”
Section: Int J Adv Res 5(12) 118-135mentioning
confidence: 99%